(8w+17)(11w-23)=0

If any individual factor on the left side of the equation is equal to 0, the entire expression will be equal to 0.

8w+17=0

11w-23=0

Set the first factor equal to 0.

8w+17=0

Subtract 17 from both sides of the equation.

8w=-17

Divide each term by 8 and simplify.

Divide each term in 8w=-17 by 8.

8w8=-178

Cancel the common factor of 8.

Cancel the common factor.

8w8=-178

Divide w by 1.

w=-178

w=-178

Move the negative in front of the fraction.

w=-178

w=-178

w=-178

Set the next factor equal to 0.

11w-23=0

Add 23 to both sides of the equation.

11w=23

Divide each term by 11 and simplify.

Divide each term in 11w=23 by 11.

11w11=2311

Cancel the common factor of 11.

Cancel the common factor.

11w11=2311

Divide w by 1.

w=2311

w=2311

w=2311

w=2311

The final solution is all the values that make (8w+17)(11w-23)=0 true.

w=-178,2311

The result can be shown in multiple forms.

Exact Form:

w=-178,2311

Decimal Form:

w=-2.125,2.09‾

Mixed Number Form:

w=-218,2111

Solve for w (8w+17)(11w-23)=0